Exploration of the HBSM MMC Five-Level Inverter for D-STATCOM Application - Ramakrishna, Elluru; Jayakrishna, Gadhamappagari; Peddakotla, Sujatha (Engineering, Technology & Applied Science Research, 2023)
This paper presents the concert exploration of a Modular Multilevel Converter (MMC) and its application for D-STATCOM. The Half Bridge (HB) sub-module is adopted in the MMC due to its simplicity and low conduction losses. An advanced modulation technique of the Phase Disposition (PD) scheme is applied for the control of the HB MMC switches. The converters are facing DC voltage balance problems under non-linear load conditions. The Proportional and Integral (PI) controller is adopted for the balance of DC voltage. Performance parameters such as apparent power, active power, reactive power, power factor, DC voltage balance, and Total Harmonics Distortion (THD) are presented and compared with the ones of the traditional two-level converter. The proposed scheme is simulated in MATLAB/Simulink.